Panentheism and the Undoing of Disenchantment - Main, Roderick (Zygon, 2017)
In this article, I draw on historical and conceptual arguments to show, first, that disenchantment and the influential view of the relationship between science and religion to which disenchantment gives rise are rooted in the metaphysics of theism. I then introduce the alternative metaphysical position of panentheism and identify Jungian psychology as an important, if implicit, mid-twentieth-century instance of panentheistic thought. Using the example of Jungian psychology, I demonstrate how the viewpoint of panentheism undoes the implications of disenchantment for the relationship between science and religion, promoting greater opportunities for dialogue and reconciliation between science and religion. I note, however, that these closer relations may depend on understanding science and religion differently from how they are understood under disenchantment. While the original tension between science and religion is eased, another tensionbetween panentheistic and disenchanted understandings of science and religionis exposed. I conclude by reflecting on some implications of this discussion for sociology.